A method for preparing hexagonal boron nitride quantum light source with the assistance of metal nanoparticles
By point-coating metal nanoparticles on the hexagonal boron nitride sheet and stimulating their plasmon resonance, combined with the strain effect, the problem of complex and high cost of preparation of hexagonal boron nitride quantum light source in the prior art is solved, and high brightness is achieved , high repeatability quantum light source preparation and on-chip integration.
Patent Information
- Application Number
- CN202411077055.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the preparation process of the hexagonal boron nitride quantum light source is complex, has high cost, and has great damage to the material, resulting in high production costs, low repeatability, and limited on-chip integration.
The method of assisting the preparation of hexagonal boron nitride quantum light source by metal nanoparticles, mechanically peeling off the two-dimensional material hBN sheet and coating metal nanoparticles on its surface. After transferring it to a silicon dioxide substrate sheet, the metal nanoparticles are excited by laser generation. Domain surface plasmon resonance reduces the migration barrier of carbon-related defects and enhances fluorescence by strain.
The preparation of quantum light source with high brightness and high repetition at low laser excitation power is realized, which reduces the preparation cost, simplifies the process, and promotes on-chip integration of quantum light sources.
Smart Images

Figure CN118610329B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of micro-nano photonic devices, and specifically relates to a method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles, and in particular to a two-dimensional material and metal nanoparticles. Background Art
[0002] Hexagonal boron nitride (hBN) is a transparent layered crystal with a wide band gap. The crystal structure of hBN is similar to that of graphene, with a honeycomb lattice and layers connected by van der Waals forces. The layered crystal structure of hBN facilitates its exfoliation into thinner two-dimensional sheets and has high anisotropy in the in-plane and out-of-plane directions. Unlike graphene, hBN is both insulating and transparent, making it an ideal material for use as an insulating layer and waveguide, and is therefore widely used in optical devices, electronic devices, and quantum devices. Quantum light sources are one of the important research and application directions of hBN. In existing research, femtosecond laser processing, ion beam processing, and electron beam irradiation are all effective means of preparing quantum light sources in hBN crystals. However, these methods are inseparable from the process of artificially introducing additional defects and thermal annealing, and there are problems such as high production cost, low repeatability of generating quantum light sources, and on-chip integration limited by destructive processing.
[0003] High-energy electron beam irradiation will produce a large number of defects in hBN materials, but the structure of these defects is often random and difficult to control accurately. This randomness will lead to unpredictable luminescence performance. In addition, high-energy electron beams will cause a certain degree of radiation damage to the hBN crystal structure, affecting the optical properties and long-term stability of the material. Although femtosecond lasers are an effective means of introducing defects in hBN materials, femtosecond laser processing equipment is complex and costly, and the defect structure produced is random; the defects of strain introduced by arrayed nanopillars, the preparation of nanopillar arrays usually requires complex lithography and etching steps, the process is cumbersome and easy to introduce additional defects and contamination, and the strain introduced by the nanopillars may be unevenly distributed in the material, resulting in spatial variations in the luminescence intensity and wavelength of the quantum light source.
[0004] Therefore, how to solve the problems of high cost and high material damage in the preparation of quantum light sources, and to provide a simple, efficient, large-scale preparation of high-brightness, high-repeatability quantum light source is a technical problem that needs to be solved urgently by technical personnel in this field. Summary of the invention
[0005] In view of the problems of the above-mentioned prior art hBN quantum light source preparation process being complicated, costly and inconvenient to integrate, the technical problem to be solved by the present invention is to provide a method for preparing hexagonal boron nitride quantum light source with the assistance of metal nanoparticles.
[0006] To this end, the above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a hexagonal boron nitride quantum light source with the aid of metal nanoparticles, characterized in that:
[0008] The following steps are involved:
[0009] S1, mechanically exfoliating the two-dimensional material hBN sheet and transferring it to the PDMS sheet substrate;
[0010] S2, coating metal nanoparticles on the surface of the hBN sheet, and then transferring the hBN and metal nanoparticles on the PDMS sheet substrate to the silicon dioxide substrate;
[0011] S2, by laser excitation of metal nanoparticles, the local surface plasmon resonance generates hot electrons, which reduce the potential barrier that carbon-related defects need to overcome in the hBN lattice, provide energy for the migration of carbon-related defects, intensify the thermal motion of carbon-related defects, and make carbon-related defects migrate and enrich in the hBN lattice, and combine to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states reduce the laser excitation power required to generate quantum light sources, while the strong localized electric field of the localized surface plasmon resonance enhances the fluorescence of the quantum light source.
[0012] While adopting the above technical solutions, the present invention may also adopt or combine the following technical solutions:
[0013] As a preferred technical solution of the present invention: the hBN sheet is a two-dimensional material mechanically peeled from a hexagonal boron nitride crystal, and has a thickness of 5-50 nm.
[0014] As a preferred technical solution of the present invention: the metal nanoparticles are applied to the surface of the hBN sheet by a pipette gun.
[0015] As a preferred technical solution of the present invention: the size of the metal nanoparticles is no more than 100 nm, the shape is cubic or rod-shaped, and the material of the metal nanoparticles is gold or silver.
[0016] As a preferred technical solution of the present invention: the laser wavelength incident on the surface of the hBN sheet and exciting the localized surface plasmon effect of the metal nanoparticles below is 400-550 nm, and the laser power density is 0.8-2 mW / μm 2 .
[0017] As a preferred technical solution of the present invention: the strain causes the frequency shift of the hBN Raman characteristic peak to be about 2 cm-1 .
[0018] As a preferred technical solution of the present invention: the strain is caused by the metal nanoparticles during the process of transferring the hBN sheet to the silicon dioxide substrate sheet.
[0019] As a preferred technical solution of the present invention: the hBN sheet is strained during the transfer to the silicon dioxide substrate, resulting in a frequency shift in the Raman characteristic peak of hBN. The strain leads to a reduction in the migration barrier during the enrichment of carbon-related defects, and the fluorescence is enhanced due to the strain.
[0020] Compared with the prior art, the invention of the method for preparing a hexagonal boron nitride quantum light source assisted by metal nanoparticles of the present invention is to use Scotch tape to mechanically peel off a two-dimensional material hBN sheet from a hexagonal boron nitride crystal, and transfer it to a PDMS sheet substrate, dot-coat the surface of the hBN sheet with metal nanoparticles, and then transfer the hBN and metal nanoparticles on the PDMS sheet substrate as a whole to a silicon dioxide substrate. Under laser excitation, the localized surface plasmons generated by the metal nanoparticles can interact with the carbon-related defects in the hBN lattice structure, and the carbon-related defects are enriched to form a quantum light source and generate fluorescence under laser excitation. At the same time, the localized surface plasmons have a Purcell effect, which enhances the fluorescence of the hBN carbon-related defect quantum light source and reduces the laser excitation power required to generate the hBN carbon-related defect quantum light source. In addition, the metal nanoparticles are located on the lower surface of the hBN sheet. Due to the presence of the metal nanoparticles, the hBN sheet undergoes a certain degree of strain during the transfer process to the silicon dioxide substrate. The strain is reflected in the frequency shift of the Raman characteristic peak of hBN, which reduces the migration barrier during the enrichment of carbon-related defects, and thus can also enhance the fluorescence of the carbon-related defect quantum light source.
[0021] The present invention introduces metal nanoparticles on the lower surface of hBN and utilizes the localized surface plasmon effect of the metal nanoparticles to reduce the migration barrier of carbon-related defects in the hBN lattice. The migration barrier is further reduced by introducing strain through the particles. Therefore, the combination of localized plasmons and strain reduces the excitation power required for the formation of the hBN carbon-related defect quantum light source. At the same time, the Purcell effect enhances the fluorescence. The invention has the advantages of low cost, simple structure and excellent performance. No destructive processing is required, so that the hBN quantum light source of the present invention is easier to realize the integration of on-chip micro-nano photonic devices, and has important application value in the fields of quantum optics, optoelectronic devices, nonlinear optics, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic structural diagram of a method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles according to Example 1 of the present invention;
[0023] Figure 2 This is a scanning electron microscope image of the gold nanocubes used in the method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles in Example 1 of the present invention;
[0024] Figure 3 Schematic diagram of the excitation and detection system of the method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles in Example 1 of the present invention;
[0025] Figure 4 The fluorescence spectrum of the method for preparing a hexagonal boron nitride quantum light source with the aid of metal nanoparticles under laser excitation according to Example 1 of the present invention;
[0026] Figure 5 The Raman spectrum of the method for preparing hexagonal boron nitride quantum light source with the aid of metal nanoparticles under laser excitation of the present invention;
[0027] Figure 6 This is a schematic structural diagram of a method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles according to Example 2 of the present invention;
[0028] Figure 7 This is a scanning electron microscope image of the gold nanorods used in the method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles in Example 2 of the present invention;
[0029] Figure 8 Schematic diagram of the excitation and detection system of the method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles in Example 2 of the present invention;
[0030] Fig. 9 This is the luminescence spectrum of the method for preparing hexagonal boron nitride quantum light source with the assistance of metal nanoparticles under laser excitation according to Example 1 of the present invention;
[0031] Fig.10 The Raman spectrum of the method for preparing hexagonal boron nitride quantum light source with the aid of metal nanoparticles under laser excitation of the present invention;
[0032] Fig.11 This is a graph showing the intensity variation of the luminescence spectrum under different polarized laser excitation when the particles used in the method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles of the present invention are gold nanocubes;
[0033] Fig.12 This is a schematic diagram of the principle of the localized surface plasmon resonance generated by metal nanoparticles in the method of the present invention for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles to generate hot electrons, reduce carbon-related defect migration enrichment and enhance fluorescence. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0035] A method for preparing a hexagonal boron nitride quantum light source with the aid of metal nanoparticles comprises the following steps: mechanically peeling a two-dimensional material hBN sheet from a hexagonal boron nitride crystal with Scotch tape, and transferring it to a PDMS sheet substrate, dotting metal nanoparticles on the surface of the hBN sheet, and then transferring the hBN and metal nanoparticles on the PDMS sheet substrate as a whole to a silicon dioxide substrate. Under laser excitation, the metal nanoparticles generate a large number of hot electrons due to localized surface plasmon resonance, and a small number of carbon-related defects are evenly distributed in the hBN. A large number of hot electrons reduce the potential barriers that the carbon-related defects need to overcome in the hBN lattice to migrate, and provide energy for the migration of carbon-related defects. The energy of a large number of hot electrons diffuses from the lattice of the metal nanoparticles to the lattice of the hBN in the form of thermal energy, aggravating the thermal motion of the carbon-related defects. Finally, under the action of the surface plasmon, a large number of carbon-related defects are enriched and combined to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states are formed to form a quantum light source and produce fluorescence under low laser power density excitation, which reduces the laser excitation power required for the generation of hBN carbon-related defect quantum light sources, which is one order of magnitude lower than direct excitation using high-power lasers. At the same time, localized surface plasmon resonance enhances the fluorescence of hBN carbon-related defect quantum light sources. In addition, the metal nanoparticles are located on the lower surface of the hBN sheet. During the transfer process, due to the presence of metal nanoparticles, the hBN sheet undergoes a certain degree of strain during the transfer process to the silicon dioxide substrate sheet. The strain is reflected in the frequency shift of the Raman characteristic peak of hBN, which reduces the migration barrier during the enrichment of carbon-related defects, and thus can also enhance the fluorescence of carbon-related defect quantum light sources. Through the processing method, hBN combined with metal nanoparticles is easier to realize the integration of on-chip micro-nano photonic devices.
[0036] Among them, hBN is hexagonal boron nitride, and PDMS is polydimethylsiloxane.
[0037] The hBN flakes are two-dimensional materials mechanically peeled from hexagonal boron nitride crystals, with a thickness of 5-50 nm.
[0038] The metal nanoparticles are applied to the surface of the hBN flakes by a pipette.
[0039] The size of the metal nanoparticles is no greater than 100 nm and the shape is cubic or rod-like.
[0040] The material of the metal nanoparticles is gold or silver.
[0041] The wavelength of the laser that is incident on the surface of the hBN sheet and excites the localized surface plasmon effect of the metal nanoparticles underneath is 400-550 nm.
[0042] The laser power density incident on the hBN surface and exciting the localized surface plasmons of the metal nanoparticles underneath is 0.8-2 mW / μm 2 , which is one order of magnitude lower than direct excitation using high-power lasers.
[0043] The quantum light source comes from the formation of localized surface plasmon resonance by metal nanoparticles, which generates a large number of hot electrons. A small number of carbon-related defects are evenly distributed in hBN. A large number of hot electrons reduce the potential barrier that carbon-related defects need to overcome in the hBN lattice to migrate, and provide energy for the migration of carbon-related defects. The energy of a large number of hot electrons diffuses from the lattice of metal nanoparticles to the lattice of hBN in the form of thermal energy, which intensifies the thermal motion of carbon-related defects. Finally, a large number of carbon-related defects are enriched under the action of surface plasmons and combined to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states, thus forming a quantum light source.
[0044] The strain causes the frequency shift of the hBN Raman characteristic peak to be about 2 cm -1 .
[0045] The strain is induced by the metal nanoparticles during the transfer of the hBN sheet to the silicon dioxide substrate sheet.
[0046] The fluorescence enhancement effect caused by strain comes from the C2C N 、C2C B , C (B)3 C N , C (N)3 C B The defect elastic stretching reduces the migration barrier during the enrichment of carbon-related defects.
[0047] Example 1
[0048] Figure 1 The schematic diagram of the method for preparing a hexagonal boron nitride quantum light source based on metal nanoparticles and strain-enhanced hexagonal boron nitride carbon-related defect luminescence is shown in Figure 1. The hexagonal boron nitride crystal (purchased from HQ Graphene) was mechanically peeled off by Scotch tape to obtain a two-dimensional material hexagonal boron nitride sheet 2, which was then transferred to a PDMS sheet substrate. The gold nanocube 1 ( Figure 1In the embodiment shown, gold nanocubes are used as an example, which are purchased from Jiaxing Najin New Materials Co., Ltd. and have an average length of 100 nm) and are applied to the surface of hexagonal boron nitride 2 by a 10 μL pipette. Figure 2 This is a scanning electron microscope image of the gold nanocubes described in this specific embodiment, which proves that the gold nanocubes used are of extremely high quality. The hexagonal boron nitride and the gold nanocubes on the PDMS thin film substrate are then transferred as a whole to the silicon dioxide substrate sheet 3. At this time, the gold nanocubes are located on the lower surface of the hexagonal boron nitride. During the transfer process, due to the presence of the gold nanocubes, the hBN thin film undergoes a certain degree of strain, and the preparation is completed.
[0049] Figure 3 Schematic diagram of the excitation and detection system of the method for preparing hexagonal boron nitride quantum light source with the aid of metal nanoparticles of the present invention, as shown in Figure 3 As shown, the hexagonal boron nitride 2 with the gold nanocube 1 underneath is placed under a microscope, and the laser 8 emits a wavelength of 500-550 nm and a power density of 0.8-2 mW / μm 2 The laser is reflected by the dichroic mirror 9, focused by the objective lens 10 and incident on the gold nanocube 1. The spectral information is collected by the objective lens 10, passes through the filter 7 and the reflector 6, and is collected by the spectrometer 5. The camera 4 is used to observe the position of the gold nanocube 1 under the hexagonal boron nitride 2.
[0050] Under laser excitation, the gold nanocube 1 generates localized surface plasmon resonance, which can enhance the nearby electric field. Due to the presence of some carbon-related defects in the lattice structure of hexagonal boron nitride 2, the gold nanocube 1 forms a localized surface plasmon resonance, generating a large number of hot electrons. A small number of carbon-related defects are evenly distributed in the hexagonal boron nitride. A large number of hot electrons reduce the potential barriers that carbon-related defects need to overcome in the hexagonal boron nitride lattice to migrate, and provide energy for the migration of carbon-related defects. The energy of a large number of hot electrons diffuses from the lattice of metal nanoparticles to the lattice of hexagonal boron nitride in the form of thermal energy, intensifying the thermal motion of carbon-related defects. Finally, under the action of surface plasmons, a large number of carbon-related defects are enriched and combined to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states form a quantum light source, which produces fluorescence under laser excitation. At the same time, due to the strain brought by the gold nanocube 1, the lattice structure of the hexagonal boron nitride 2 is stretched to a certain extent, resulting in a frequency shift of the Raman characteristic peak, such as Figure 4 As shown, it should have been about 1366.59 cm as shown by the dotted line -1 The Raman peak produced about 2cm -1The frequency shift becomes about 1364.17 cm as shown by the solid line. -1 , proving the strain caused by the presence of gold nanocube 1. The localized surface plasmons generated by gold nanocube 1 enrich the carbon-related defects and produce fluorescence. Under the combined effect of the localized surface plasmons introduced by gold nanocube 1 and the strain, the fluorescence of the carbon-related defect quantum light source is greatly enhanced, while the potential barrier of the migration of the hexagonal boron nitride carbon-related defect quantum light source is reduced. Figure 3 The spectrum of the peak is 581.49 nm, and Figure 4 The peak is at 1330 cm -1 and 1602.10 cm -1 The Raman peak of 573.04 nm can prove that the fluorescence comes from the carbon-related defects in the lattice structure of hexagonal boron nitride 2, and the luminescence is enhanced by the gold nanocube 1. The luminescence peak of 573.04 nm is the Raman peak of hexagonal boron nitride 2. This proves that the present invention provides a method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles.
[0051] Example 2
[0052] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0053] Figure 6 The schematic diagram of the method for preparing a hexagonal boron nitride quantum light source based on metal nanoparticles and strain-enhanced hexagonal boron nitride carbon-related defect luminescence is shown in Figure 1. The hexagonal boron nitride crystal (purchased from HQ Graphene) was mechanically peeled off by Scotch tape to obtain a two-dimensional material hexagonal boron nitride sheet 12, which was transferred to a PDMS sheet substrate. The gold nanorods 11 ( Figure 6 In the embodiment shown, gold nanorods are taken as an example, which are purchased from NanoSeedz, with an average length of 100 nm and an average width of 40 nm, and are applied to the surface of hexagonal boron nitride 12 by a 10 uL pipette. Figure 2 This is a scanning electron microscope image of the gold nanorods described in this specific embodiment, which proves that the gold nanorods used are of extremely high quality. The hexagonal boron nitride and the gold nanorods on the PDMS thin film substrate are then transferred as a whole to the silicon dioxide substrate sheet 13. At this time, the gold nanorods are located on the lower surface of the hexagonal boron nitride. During the transfer process, due to the presence of the gold nanorods, the hBN thin film undergoes a certain degree of strain, and the preparation is completed.
[0054] Figure 8 Schematic diagram of the excitation and detection system of the method for preparing hexagonal boron nitride quantum light source with the aid of metal nanoparticles of the present invention, as shown in Figure 8 As shown, the hexagonal boron nitride 12 with the gold nanorods 11 underneath is placed under a microscope, and the laser 18 emits a wavelength of 500-550 nm and a power density of 0.8-2 mW / μm2 The laser is reflected by the dichroic mirror 20. The lens 19 is a half-wave plate that can adjust the polarization of the laser. The laser is focused by the objective lens 21 and incident on the gold nanorod 11. The spectral information is collected by the objective lens 21, passes through the filter 17 and the reflector 16, and is collected by the spectrometer 15. The camera 14 is used to observe the position of the gold nanorod 11 under the hexagonal boron nitride 12.
[0055] Under laser excitation, the gold nanorods 11 generate localized surface plasmon resonance, which can enhance the nearby electric field. Due to the presence of some carbon-related defects in the lattice structure of hexagonal boron nitride 12, the gold nanorods 11 form localized surface plasmon resonance, generating a large number of hot electrons, while a small number of carbon-related defects are evenly distributed in hexagonal boron nitride. A large number of hot electrons reduce the potential barriers that carbon-related defects need to overcome in the hexagonal boron nitride lattice to migrate, and provide energy for the migration of carbon-related defects. In addition, the energy of a large number of hot electrons diffuses from the lattice of metal nanoparticles to the lattice of hexagonal boron nitride in the form of thermal energy, intensifying the thermal motion of carbon-related defects. Finally, under the action of surface plasmons, a large number of carbon-related defects are enriched and combined to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states form a quantum light source, which produces fluorescence under laser excitation. At the same time, due to the strain brought by the gold nanorods 11, the lattice structure of hexagonal boron nitride 12 is stretched to a certain extent, resulting in a frequency shift of the Raman characteristic peak, such as Fig. 9 As shown, it should have been about 1366.59 cm as shown by the dotted line -1 The Raman peak produced is about 2 cm -1 The frequency shift becomes about 1364.17 cm as shown by the solid line. -1 , proving the strain caused by the presence of gold nanorods 11. Gold nanorods 11 generate localized surface plasmons that enrich carbon-related defects and generate fluorescence. Under the combined effect of localized surface plasmons introduced by gold nanorods 11 and strain, the fluorescence of carbon-related defect quantum light sources is greatly enhanced, while the potential barrier for the migration of carbon-related defect quantum light sources in hexagonal boron nitride is reduced. Fig.10 The spectrum of the peak is 581.72 nm, and Fig. 9 The peak is at 1330 cm -1 and 1602.10 cm -1 The Raman peak of 573.81 nm can prove that the fluorescence comes from the carbon-related defects in the lattice structure of hexagonal boron nitride 12, and the luminescence is enhanced by the gold nanorods 11. The luminescence peak of 573.81 nm is the Raman peak of hexagonal boron nitride 12. This proves that the present invention provides a method for preparing hexagonal boron nitride quantum light source with the assistance of metal nanoparticles. In addition, Fig.11 In the graph of the change in luminescence spectrum intensity under different polarization laser excitation, the corresponding fluorescence intensity has an extreme change every time the polarization rotates 90°, which is consistent with the polarization characteristics of gold nanorods, proving the fluorescence enhancement effect of gold nanorods.
[0056] Fig.12 The schematic diagram of the principle of the local plasmon resonance generated by the metal nanoparticles in the method of preparing the hexagonal boron nitride quantum light source with the assistance of metal nanoparticles of the present invention generates hot electrons, which participate in the enrichment and fluorescence of carbon defects. Under laser excitation, the metal nanoparticles form a local surface plasmon resonance, generating a large number of hot electrons 22, and a small number of carbon-related defects are evenly distributed in the hexagonal boron nitride. The large number of hot electrons reduces the barrier that the carbon-related defects need to overcome in the hexagonal boron nitride lattice to migrate, and provides energy for the migration of carbon-related defects. The energy of a large number of hot electrons diffuses from the lattice of the metal nanoparticles to the lattice of the hexagonal boron nitride in the form of thermal energy, aggravating the thermal motion of carbon-related defects. Finally, under the action of the surface plasmon, a large number of carbon-related defects are enriched and combined to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states form a quantum light source and produce fluorescence under low laser excitation, which reduces the laser excitation power required to generate hexagonal boron nitride carbon-related defect quantum light sources by an order of magnitude compared to direct excitation using high-power lasers.
[0057] In the present invention, generally, the two-dimensional material hexagonal boron nitride flakes are obtained by mechanically peeling off the hexagonal boron nitride crystals with adhesive tape, and the thickness is 5-50 nm. The laser wavelength is 500-550 nm, and the power is 0.8-2 mW / μm 2 The material of metal nanoparticles is usually gold or silver, and the shape of metal nanoparticles is usually cube or rod.
[0058] The invention discloses a method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles, comprising the following steps: transferring a two-dimensional material hexagonal boron nitride sheet to a PDMS sheet substrate, dotting metal nanoparticles, and then transferring the hBN sheet and the metal nanoparticles on the polyPDMS substrate as a whole to a silicon dioxide substrate; activating defects in the hBN sheet with a laser to generate a quantum light source, and under the action of the metal nanoparticles, the quantum light source is enhanced. The invention relates to a method for preparing a hexagonal boron nitride quantum light source with the assistance of metal nanoparticles, wherein the metal nanoparticles generate a localized surface plasmon resonance effect under laser excitation, and the hot electrons generated by the metal nanoparticles enrich the carbon-related defects in the hBN sheet to form a quantum light source and generate fluorescence, and the localized surface plasmon effect enhances the luminescence and Raman scattering intensity of the quantum light source of the carbon-related defects, and the metal nanoparticles located below the hBN sheet cause a certain degree of strain in the hBN, and the strain reduces the potential barrier for migration during the enrichment of carbon-related defects, reduces the required activation energy for the formation of carbon-related defects, and further enhances the fluorescence. The method for preparing a hexagonal boron nitride quantum light source with the aid of metal nanoparticles of the present invention has the characteristics of simple steps, high repeatability, simple structure, low cost and good enhancement effect. In addition, no destructive processing is required, making the hBN quantum light source of the present invention easier to integrate into an on-chip micro-nano photonic device.
[0059] The above-mentioned specific implementation methods are used to explain the present invention and are only preferred embodiments of the present invention, rather than limiting the present invention. Any modifications, equivalent substitutions, improvements, etc. made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a hexagonal boron nitride quantum light source assisted by metal nanoparticles, characterized in that: The following steps are involved: S1, mechanically exfoliating the two-dimensional material hBN sheet and transferring it to the PDMS sheet substrate; S2, coating metal nanoparticles on the surface of the hBN sheet, and then transferring the hBN sheet and the metal nanoparticles on the PDMS sheet substrate to the silicon dioxide substrate; S3, by laser excitation of metal nanoparticles, the local surface plasmon resonance generates hot electrons, which reduce the potential barrier that carbon-related defects need to overcome in the hBN thin film lattice, provide energy for the migration of carbon-related defects, intensify the thermal motion of carbon-related defects, and make carbon-related defects migrate and enrich in the hBN thin film lattice, and combine to form C2C with lower formation energy. N 、C2C B , C (B)3 C N , C (N)3 C B A series of carbon-related defect states reduce the laser excitation power required to generate quantum light sources, while the Purcell effect of localized surface plasmon resonance enhances the fluorescence of quantum light sources; The hBN sheet with metal nanoparticles on the surface is strained during the transfer process to the silicon dioxide substrate, causing the Raman characteristic peak of the hBN sheet to shift in frequency. The strain leads to a reduction in the migration barrier during the enrichment of carbon-related defects, thereby leading to the fluorescence enhancement of the carbon-related defect quantum light source. hBN is hexagonal boron nitride and PDMS is polydimethylsiloxane.
2. The method for preparing a hexagonal boron nitride quantum light source assisted by metal nanoparticles according to claim 1, characterized in that: The hBN flakes are two-dimensional materials mechanically peeled from hexagonal boron nitride crystals, with a thickness of 5-50 nm.
3. The method for preparing a hexagonal boron nitride quantum light source with the aid of metal nanoparticles according to claim 1, characterized in that: The metal nanoparticles are applied onto the surface of the hBN flakes by a pipette.
4. The method for preparing a hexagonal boron nitride quantum light source assisted by metal nanoparticles according to claim 1, characterized in that: The size of the metal nanoparticles is no more than 100 nm, and the shape is a cube or a rod. The material of the metal nanoparticles is gold or silver.
5. The method for preparing a hexagonal boron nitride quantum light source assisted by metal nanoparticles according to claim 1, characterized in that: The laser wavelength incident on the surface of the hBN sheet and stimulating the localized surface plasmon effect of the metal nanoparticles underneath is 400-550 nm, and the laser power density is 0.8-2 mW / μm 2 .
6. The method for preparing a hexagonal boron nitride quantum light source with the aid of metal nanoparticles according to claim 1, characterized in that: The strain causes the frequency shift of the Raman characteristic peak of hBN thin film to be about 2 cm -1 .
Citation Information
Patent Citations
Deep ultraviolet photoelectric detector and preparation method and application thereof
CN114551626A
Monocrystal hBN nanosphere array and preparation method thereof
CN115976638A